Exchange rate volatility without the contrivance of fundamentals and the failure of PPP - Mikael Bask (Bank of Finland, 2006)
Since the magnitude of exchange rate overshooting may not be the same for different exchange rates of a currency, a monetary expansion or contraction in, for example, the EMU, will affect the exchange rate between the U.S. dollar and the yen, even though there are no changes in monetary fundamentals in the U.S. or Japan. This fact is demonstrated in a sticky-price monetary model due originally to Dornbusch (1976) that is enlarged with currency traders that use Chartism in the form of moving averages.It is also demonstrated that purchasing power parity (PPP) does not necessarily hold in long-run equilibrium.These results are interesting since, according to the empirical literature, there are often large movements in nominal exchange rates that are apparently unexplained by macroeconomic fundamentals, and there is also a weak support for PPP.
URN:NBN:fi:bof-20140807285
Keywords: F31; F41; 330; Chartism; foreign exchange; macroeconomic fundamentals; moving averages; overshooting and PPP